Effect of Varying Dietary Protein on Food Utilization, Growth Performance and Body Composition of Major Carp (Labeo rohita) - Mahajan, Shashikant (Indian Journal of Animal Nutrition, 2018)
Three fish meal based pelleted diets containing 27% (A), 31% (B) and 35% (C) crude protein levels were evaluated for Major carp (Labeo rohita) early fry (450) after dividing into three groups of 3 replicates with 50 carps each in a aquaria through a short term laboratory experiment of three weeks. The food consumption (%) was lowest in major carp fed on highest protein diet, while highest in 31% CP although numerically comparable. Food conversion and protein efficiency ratios were 2.75, 1.36, 2.74, 1.19 and 2.53, 1.14 in group A, B and C respectively with no significant difference among groups. Average weight gain % was highest (228.16) in group B though numerically comparable among groups. The digestibility of dry matter, organic matter and crude protein were highest in group C as compared to others, while numerically data remained comparable. Body composition of major carp also indicated numerical superiority (high protein and low AIA content) of group fed 35% CP although data were statistically comparable among the groups.Â Non significant variation in food conversion, protein efficiency ratio as well as protein retention efficiency suggests suitability of lowest protein level.Â On the basis of performance recorded in the present experiment it may be concluded that 27% CP with high carbohydrate (47.97%) may be optimum (77.01 Protein / Energy ratio) to support performance in early fry of major carp fed fish meal based pelleted diets.